Microstructured superhydrophobic anti-reflection films for performance improvement of photovoltaic devices. (July 2017) - Wang, Min; Gu, Xuehao; Ma, Pengsha; Zhang, Weikang; Yu, Dongliang; Chang, Paichun; Chen, Xiaoyuan; Li, Dongdong
Graphical abstract: Anti-reflection and superhydrophobic film was fabricated by a facile hot embossing process, which shows a contact angle of 155° and improves the daily energy output of solar cells by10.1%. Highlights: Omnidirectional anti-reflection and superhydrophobicity (AR-S) film was fabricated by a facile hot embossing process. The micro-pillars on the AR-S film show an improved mechanical robustness compared with nanostructures. The AR-S film increases the daily energy output of solar cells by 10.1%. Abstract: Highly durable anti-reflection and superhydrophobic (AR-S) functional film as solar panel surface material is desirable to reduce the panel cleaning cost and boost the performance of energy generation. Herein, we fabricated flexible plastic AR-S films with three-dimensional (3-D) micro-pillar arrays by a facile hot embossing lithography process, which can be potentially used for different variety of photovoltaic devices. In this work, the AR-S films are integrated with commercial polycrystalline silicon solar cells for demonstration purpose. The AR-S film works as an effective medium to enhance photo generation rates is also confirmed by numerical simulation that results in a broadband and omnidirectional enhanced performance.